Establishment of space syntax to read urban road network; the case of Sari, Iran - Ehsan Valipour; Samira Tayyebisoudkolaei; Abdolah Mobaraki (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
Cities have permanent changes as a living organism, where the transformation required in designing a solution for structural and social demands achieving safe and healthy human contacts. Some scholars divide city sustainable development toward two main views, as the building's set are connected by a space, on the other hand, human social actions are linked by urban network interaction. The aim of this paper is to study on the urban road network by the establishment of space syntax logic, this issue is divided into two main parts, as a first part, the study on already existing and the second part is bringing the new suggestions to a more qualified urban road network. Sari city of Iran is selected for this Case Study.